(untitled) (Journal of Environmental Microbiology and Toxicology, 2014)
Of all heavy metals, molybdenum is one of the very toxic metals ions to ruminants with level as low as several parts per million could cause death. It is an emerging pollutant. It is also toxic to the spermatogenesis process with several animal model showed its toxic property and hence, is of great concern. Previously, a molybdenum-reducing bacterium Bacillus sp. strain A.rzi has been isolated and its kinetics of reduction studied with the best model to fit the curve is the Luong model. The use of this and other nonlinear regression model and further statistical analyses to find the best model relies on the facts that the residuals (difference between observed and predicted data) followed a normal distribution and that the data must be free of outliers and the variance homogenous (homoscedasticity). If all of these assumptions are satisfied, the test is said to be robust. In this work we perform statistical diagnostics to the residuals to satisfy the requirements above and found that the residuals conformed to all of the requirements above indicating the Luong model is a robust model for modelling molybdenum reduction in the bacterium.